2011
DOI: 10.1007/s12571-010-0100-5
|View full text |Cite
|
Sign up to set email alerts
|

The future role of agriculture in the Arab region’s food security

Abstract: Journal articleIFPRI3; ISI; PICEPTD; DGO; PICP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…To explore the role of increased agricultural productivity for food security in Africa, we use IFPRI’s IMPACT system of models (Robinson et al, 2015). IMPACT has been used extensively in projecting future agricultural production and demand and changes to food security globally and regionally (Delgado et al, 2001, Nelson et al, 2010, Rosegrant et al, 1999, Rosegrant et al, 2001, Sulser et al, 2011). It has been used to explore alternative agricultural productivity futures (Islam et al, 2016, Rosegrant et al, 2014), including the potential impacts of climate change on agriculture (Ignaciuk and Mason-D'Croz, 2014, Nelson et al, 2010, Sulser et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…To explore the role of increased agricultural productivity for food security in Africa, we use IFPRI’s IMPACT system of models (Robinson et al, 2015). IMPACT has been used extensively in projecting future agricultural production and demand and changes to food security globally and regionally (Delgado et al, 2001, Nelson et al, 2010, Rosegrant et al, 1999, Rosegrant et al, 2001, Sulser et al, 2011). It has been used to explore alternative agricultural productivity futures (Islam et al, 2016, Rosegrant et al, 2014), including the potential impacts of climate change on agriculture (Ignaciuk and Mason-D'Croz, 2014, Nelson et al, 2010, Sulser et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Developing countries such as Indonesia often relying on imported food is not a wise choice because it is not sustainable. Importing is a short-term solution for food shortage and/or securing food availability ( Sulser et al, 2011 ).…”
Section: Food Security In Indonesiamentioning
confidence: 99%
“…The government plays an important role in protecting the price and system through regulations (Lele and Goswami, 2020). Food security is closely related to trade, demand, and price (Sulser et al, 2011). Problems arising from agriculture and the food-supply chain are widespread food shortage and sharp price increases (Altieri and Nicholls, 2020), serious problems for food security (Savary et al, 2012).…”
Section: Food Security Post-covid-19mentioning
confidence: 99%
“…Importing food is one solution to meeting demand. But, as Mukiibi (2020) and Sulser et al (2011) suggested, broad food imports make countries dependent on imported food. Limitations on exports and imports during the pandemic applied have meant that countries relying on imported food are more vulnerable to food insecurity due to difficulties importing food.…”
Section: Food Security Post-covid-19mentioning
confidence: 99%